Neural Indices of Semantic Processing in Early Childhood Distinguish Eventual Stuttering Persistence and Recovery - Kreidler, Kathryn (J Speech Lang Hear Res, 2017)
PURPOSE: Maturation of neural processes for language may lag in some children who stutter (CWS), and event-related potentials (ERPs) distinguish CWS who have recovered from those who have persisted. The current study explores whether ERPs indexing semantic processing may distinguish children who will eventually persist in stuttering (CWS-ePersisted) from those who will recover from stuttering (CWS-eRecovered). METHOD: Fifty-six 5-year-old children with normal receptive language listened to naturally spoken sentences in a story context. ERP components elicited for semantic processing (N400, late positive component [LPC]) were compared for CWS-ePersisted, CWS-eRecovered, and children who do not stutter (CWNS). RESULTS: The N400 elicited by semantic violations had a more focal scalp distribution (left lateralized and less anterior) in the CWS-eRecovered compared with CWS-ePersisted. Although the LPC elicited in CWS-eRecovered and CWNS did not differ, the LPC elicited in the CWS-ePersisted was smaller in amplitude compared with that in CWNS. CONCLUSIONS: ERPs elicited in 5-year-old CWS-eRecovered compared with CWS-ePersisted suggest that future recovery from stuttering may be associated with earlier maturation of semantic processes in the preschool years. Subtle differences in ERP indices offer a window into neural maturation processes for language and may help distinguish the course of stuttering development.